Religious and Numinous Practices in the Novel Pomegranate Bloom - Wang, Aiqing (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2024)
A novel entitled 石榴花开 Shiliu Huakai ‘Pomegranate Bloom’ (Trans. Mine) (2019) falls into a literary subgenre 乡土文学 xiangtu wenxue ‘native-soil literature’ and it is composed by a Shandong-born fictionist 耿雪凌 Geng Xueling (1968- ). Apart from salient folk attributes paining a vivid portrait of the rural area of southwest Shandong, Pomegranate Bloom is also featured by numinous depictions pertaining to paranormal forces and occult deeds. To be more specific, the narrative encompasses rituals and deities of the institutionalised Taoism and Buddhism, practitioners of esoteric arts and magical powers correlated to popular religion, animal worship and shamanistic curse, a veritable cornucopia of divinatory acts, as well as folk remedies that are surmised to be justified by traditional Chinese medicine.